Safety and Efficacy of Pre-Cytoreduction Prior to Definitive Multi-Agent Chemotherapy in Aggressive Lymphoma - Reena Kumari Sunil; Tariq Siddique; Sunil Kumar; Samina Shamim (ziauddin University, 2024)
ABSTRACT Background: Pre-cytoreduction refers to the administration of initial chemotherapy to reduce tumor burden prior to initiating definitive multi-agent chemotherapy. This study assessed the safety and efficacy of pre-cytoreduction prior to definitive multi-agent chemotherapy in aggressive lymphomas. Methods: A prospective cohort study was done at Ziauddin Hospital, Karachi for six months. Patients of either gender, aged between 18-80 years diagnosed with aggressive lymphoma (Stage II-IV) were included. Patients having stage-I lymphoma, primary CNS lymphoma, HIV-linked Diffuse Large B Cell Lymphoma (DLBCL) transformed lymphoma, and other malignancies were excluded. The pre-cytoreduction group received a low dose of chemotherapeutic drug on the −6th day and prednisolone 100mg daily for 7 days (−6th day to day 0) followed by standard chemotherapy on day 1. Non-pre-cytoreduction group received chemotherapy without pre-cytoreduction. After chemotherapy's first cycle, follow-up was done for 30 days. Anxiety assessment was done using the Hamilton Anxiety Rating Scale (HAM-A). For data analysis, SPSS v27 was used. Results: From 120 patients, 27(22.5%) were diagnosed with Burkitt Lymphoma while 93(77.5%) with DLBCL. Pre-cytoreduction included prednisone, in 17(14.2%) patients, while 12(10%), 13(11%), and 10(8%) were given Vincristine, Prednisolone (VP), Cyclophosphamide, Prednisolone (CP) and Cyclophosphamide, Vincristine, and Prednisolone (CVP) respectively. There was a significant difference between both groups' tumor lysis syndrome, bone marrow suppression, ECOG PS (Eastern Cooperative Oncology Group Performance Status), and other post-treatment complications (p<0.001). Conclusion: Pre-cytoreduction was reported to be slightly better than conventional therapy in terms of compliance, with pre-cytoreduction improving patients' performance status, decreased hospital emergency visits, febrile neutropenia risk, and improved treatment response rates.